Associations of Upper Arm and Thigh Circumferences with Dementia and Depression in Korean Elders - Lee, Yong-Seong (Psychiatry Investig, 2017)
OBJECTIVE: Previous studies have reported an association between weight loss and cognitive impairment. Changes in anthropometric measurements, such as arm and thigh circumferences, are associated with body mass changes and physical activity. Our aim was to investigate the association of upper arm and thigh circumferences with dementia and depression in the community-dwelling elderly population. METHODS: In total, 2,498 community residents aged 65 years or over were clinically assessed for dementia using the Korean version of the Community Screening Interview for Dementia. Depression was also assessed using the Korean version of the Geriatric Mental State Schedule B3. Arm and thigh circumferences were measured. Complex sample logistic regression was performed to evaluate associations of changes in anthropometric measurements with dementia/depression after controlling for other covariates. RESULTS: In the adjusted analyses, there was an independent association between dementia and arm circumference (OR=1.12; 95% CI=1.06–1.19). This association was significant in the females (OR=1.12; 95% CI=1.05–1.19) but not in males (OR=1.07; 95% CI=0.93–1.28). The association between dementia and thigh circumference was not significant in the adjusted analysis (OR=1.03; 95% CI=0.99–1.07). No significant association was found between either upper arm or thigh circumference and depression. CONCLUSION: In the older female Korean population, decreased upper arm circumference was associated with dementia and may represent a biological marker for this condition. This association may be explained by nutritional deficits or decreased physical activity.